2020
DOI: 10.1159/000506406
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional Pathways between Attachment, Mentalizing, and Posttraumatic Stress Symptomatology in the Context of Childhood Trauma

Abstract: Introduction: Exposure to traumatic stressful events in childhood is an important risk factor for the development of posttraumatic symptomatology. From a mentalization-based developmental perspective, childhood adversity can affect attachment in children and may result in insecure attachment and impaired mentalizing abilities, which increase the lifetime risk for psychopathology. The present cross-sectional study examined the potential mediating role of attachment insecurity and impaired mentalizing on the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…Moreover, several mediation models (e.g. Huang et al, 2020;Chiesa & Fonagy,2014) showed a partial mediating effect of adverse childhood experiences on general psychopathology via mentalizing. In detail mentalizing had a protective, buffering effect which leads to a decrease in general psychopathology.…”
Section: Empirical Evidence Of Mentalizing As a Protective Mechanismmentioning
confidence: 99%
“…Moreover, several mediation models (e.g. Huang et al, 2020;Chiesa & Fonagy,2014) showed a partial mediating effect of adverse childhood experiences on general psychopathology via mentalizing. In detail mentalizing had a protective, buffering effect which leads to a decrease in general psychopathology.…”
Section: Empirical Evidence Of Mentalizing As a Protective Mechanismmentioning
confidence: 99%
“…The aim of the present research is to replicate and extend previous findings from Spitzer and colleagues, while also comprehensively presenting our concerns regarding the measure. A critical reexamination and discussion of the RFQ-8 appears to be of particular importance given that researchers are increasingly adopting the measure for primary investigations of the mentalizing construct (e.g., Agostini et al, 2019;Badoud et al, 2018;Berthelot et al, 2019;Brugnera et al, 2020;Carlone & Milan, 2020;Cosenza et al, 2019;de Meulemeester et al, 2017de Meulemeester et al, , 2018Euler et al, 2019;Gambin et al, 2020;Huang et al, 2020;Li et al, 2020;Macfie et al, 2020;Morosan et al, 2019Morosan et al, , 2020Perroud et al, 2017;Sacchetti et al, 2019;Salaminios et al, 2020;Scandurra et al, 2020) or as an outcome measure for evaluating psychotherapy effectiveness (e.g., Arnfred et al, 2017;Derks et al, 2019).…”
mentioning
confidence: 99%
“…Social embedded stress response may enforce the pathway between dissociation and mentalization in patients with attachment insecurity. This theory is supported by recent a recent study, which showed that attachment insecurity in combination with lower mentalizing mediated the link between childhood trauma and PTSD symptoms in adults who had experienced childhood neglect and abuse (24). Early maltreatment may increase the risk for the development of attachment insecurity with long-lasting effects.…”
Section: Discussion/conclusionmentioning
confidence: 56%
“…Sharp et al describe a socialcognitive model of PTSD and attachment insecurity with impaired mentalizing abilities mediated associations with dissociative experiences (26). Individuals with lower mentalizing predict dissociation after exposure to childhood trauma (24). There may be a link between related mentalizing process early maltreatment and later posttraumatic symptoms such as dissociative experience.…”
Section: Discussion/conclusionmentioning
confidence: 99%